Case Study on: ABC Cement Co. Ltd Prospect of Myanmar as the Export Destination - Chee, Chee Meng (1997)
This paper is one the case study of cement industry in Malaysia - present and future situation, as well as the cement industry in ASEAN. There are a lot of informations required in order to come-up with a near accurate analysis for the readers on the industry's movement in this region. We would like to take this opportunity to thank C & CA (Malaysia Cement Association), ACPAC (Asia Cement Producers Committee), Myanmar Investment Corporation, Myanmar Port Authority, and variuos international consultant's assistant on the datas and information supplied. After the detail analysis, we foresee the cement supply situation in year 1998 will be at the surplus situation; it might be due to more cement plants either a complete plant or grinding plant, cement terminal, cement silos are coming up with the aggresive investment from new comers from year 1997 to 2000.